Doxorubicin-loaded ionic liquid–polydopamine nanoparticles for combined chemotherapy and microwave thermal therapy of cancer. Issue 39 (1st April 2016) - Tang, Wenting; Liu, Bo; Wang, Shengping; Liu, Tianlong; Fu, Changhui; Ren, Xiangling; Tan, Longfei; Duan, Wubiao; Meng, Xianwei
Abstract : Doxorubicin-loaded ionic liquid–polydopamine (IL–PDA–DOX) nanocomposites were obtained with high antitumor efficacy for combined chemotherapy and microwave thermal therapy of cancer. Abstract : Recently, combinational therapy has been increasingly employed in the treatment of cancer. In this study, hollow polydopamine nanoparticles were developed as favorable biocompatible delivery nanoplatforms for chemotherapy and microwave thermal therapy. By loading polydopamine nanoparticles with ionic liquid, the functionalized polydopamine nanoparticles became chemotherapeutic drug nanocarriers for combinational therapy. The obvious antitumor efficacy of doxorubicin-loaded ionic liquid–polydopamine nanocomposites was demonstrated in in vitro and in vivo experiments for combined chemotherapy and microwave thermal therapy. Moreover, the combination of chemotherapy with microwave thermal therapy applied to cancer therapy based on drug-loaded ionic liquid–polydopamine nanocomposites is a promising therapy for future cancer treatment in clinical applications.